1999
DOI: 10.1164/ajrccm.159.3.9804027
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lung Injury in Preterm Lambs

Abstract: The cause of chronic lung disease of early infancy, often called bronchopulmonary dysplasia (BPD), remains unclear, partly because large-animal models that reliably reproduce BPD have not been available. We developed a model of BPD in lambs that are delivered prematurely and ventilated for 3 to 4 wk after birth to determine whether the histopathology of chronic lung injury in premature lambs mimics that which occurs in preterm infants who die with BPD, and to compare two ventilation strategies to test the hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(83 citation statements)
references
References 41 publications
2
77
0
4
Order By: Relevance
“…van Heeckeren et al (10) demonstrated lower measurable lung volumes to inflation and an increased number of neutrophils in alveolar washes of preterm lambs after ventilation with a moderate amount of oxygen for a 2-h period compared with no ventilation or CPAP for 2 h. Ventilation for 30 min after birth with high compared with low tidal volumes leads to persistently decreased lung compliance in preterm lambs (15). In preterm lambs, a 3-4 wk period of mechanical ventilation has been shown to disrupt lung development and produce histopathologic changes including greater smooth muscle thickness around terminal bronchioles similar to lungs of preterm infants dying of BPD (16). After several weeks of mechanical ventilation in the preterm baboon, decreased alveolarization is observed (17).…”
Section: Discussionmentioning
confidence: 99%
“…van Heeckeren et al (10) demonstrated lower measurable lung volumes to inflation and an increased number of neutrophils in alveolar washes of preterm lambs after ventilation with a moderate amount of oxygen for a 2-h period compared with no ventilation or CPAP for 2 h. Ventilation for 30 min after birth with high compared with low tidal volumes leads to persistently decreased lung compliance in preterm lambs (15). In preterm lambs, a 3-4 wk period of mechanical ventilation has been shown to disrupt lung development and produce histopathologic changes including greater smooth muscle thickness around terminal bronchioles similar to lungs of preterm infants dying of BPD (16). After several weeks of mechanical ventilation in the preterm baboon, decreased alveolarization is observed (17).…”
Section: Discussionmentioning
confidence: 99%
“…In recent pathologic reports, BPD is characterized by decreased alveolar development resulting in large saccular airspaces (1)(2)(3) that are thought to result from the superposition of injury on the developing lung (4). Similar morphologic alterations with alveolar hypoplasia, variable amounts of saccular wall fibrosis, and dysmorphic capillary development occur in oxygen-exposed newborn mice and ventilated preterm baboons and sheep (5)(6)(7). Although there are differences in the histopathology of BPD before the era of surfactant treatment and newer approaches to more gentle ventilation of preterm infants and more recent descriptions of BPD (1,3), inflammation appears to be a common factor (8).…”
mentioning
confidence: 85%
“…Estudos experimentais demonstraram que a ventilação mecânica e o oxigênio podem interferir no desenvolvimento alveolar e vascular de animais prematuros [16][17][18] . Em prematuros, a atividade das enzimas antioxidantes, como a super-óxido desmutase, a catalase e a peroxidase, é relativamente deficiente, tornando-os mais vulnerá-veis à toxicidade ao oxigênio 19 .…”
Section: Toxicidade Do Oxigêniounclassified